Hybrid Teaching: Conceptualization Through Practice for the Post COVID19 Pandemic Education - Ulla, Mark Bedoya; Perales, William Franco (Frontiers in Education, 2022)
While a number of studies have previously conceptualized hybrid teaching, often used interchangeably with blended learning during the pre-COVID19 pandemic, hybrid teaching has been undertheorized and unexplored during and post-COVID19 pandemic when schools have slowly opened their classrooms for students. This paper explores the concept of hybrid teaching (also referred to as hybrid classroom instruction and hybrid learning) and how such teaching methodology is different from blended learning, fully online, and remote teaching by presenting a teacher’s practice during the COVID19 pandemic. Although our goal is to identify clearly what hybrid teaching is, we do not intend to offer a definite conceptualization and practice of hybrid teaching as teaching is context-dependent. However, we argue that hybrid teaching has the potential to be one of the teaching methodologies in the post COVID19 pandemic education, especially when schools and universities are in the transition back to residential classroom teaching.